PROFIL PEMAHAMAN KONSEP SISWA PADA MATERI PERBANDINGAN TRIGONOMETRI DI KELAS X SMA NEGERI 1 TIKKE RAYA DITINJAU DARI GAYA BELAJAR: Profile of understanding concept of students on the comparison of trigonometry material of class X SMA Negeri 1 Tikke Raya reviewed through the learning styles - Annisa; Ismaimuza, Dasa; Paloloang, Baharuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to obtain a profile description of students' conceptual understanding of comparative trigonometry material in class X IPA SMA Negeri 1 Tikke Raya in terms of learning style. This type of research is descriptive with a qualitative approach. The subjects of this study consisted of 3 students of class X who have visual, auditory and kinesthetic learning styles. Data collection was carried out by providing learning style questionnaires, written tests, and interviews. The results of this study indicated that: (1) restated the concepts that had been studied by the auditory subject to write down the trigonometric comparison formula completely and correctly, the visual subject could not write the trigonometric comparison formula completely, and the kinesthetic subject could not write the trigonometry comparison formula; (2) Classifying objects based on whether the requirements that form the concept are fulfilled or not, visual, auditory, and kinesthetic subjects are able to classify sin, cos, tan, cosec, sec, and tan based on their angle; (3) Give examples or non-examples of the concepts being studied, namely visual, auditory, and kinesthetic subjects distinguishing the application and non-application of trigonometry in everyday life; (4) Presenting concepts in the form of pictures, namely visual, auditory, and kinesthetic subjects are able to illustrate questions in the form of sketches of right-angled triangles; (5) in applying the concept logically, visual, auditory, and kinesthetic subjects use the Pythagorean formula to determine the value of the side length of a right triangle.